Blood pressure course in acute stroke relates to baroreflex dysfunction - Sykora, Marek; Diedler, Jennifer; Poli, Sven; Rupp, André; Turcani, Peter; Steiner, Thorsten (Cerebrovascular diseases, 2010)
Background: Acute hypertension frequently occurs in acute stroke and is associated with unfavorable outcome. However, despite the high prevalence, the pathophysiology remains unclear. Baroreflex dysfunction has repeatedly been reported in stroke patients. We hypothesize that blood pressure (BP) derangements in the acute phase relate to the impairment of baroreflex. Methods: We assessed baroreflex sensitivity (BRS) in 109 acute stroke patients with both ischemic and hemorrhagic stroke using the sequential cross-correlation method. Admission BP and BP values derived from continuous 72-hour monitoring were recorded. Demographic and clinical data including stroke volumes and admission NIHSS scores were included into the analysis. Results: The BRS significantly correlated with admission BP (r = -0.24, p = 0.01), with the occurrence of acute hypertension (≧220mm Hg/≧ 110 mm Hg) on admission (r = -0.37, p < 0.001) and with the number of episodes with ≧220 mm Hg/≧110 mm Hg in the first 72 h after admission (r = -0.44, p < 0.001). Admission NIHSS or lesion volume did not correlate with acute hypertension on admission or hypertensive episodes within the first 72 h. In a multivariable model, BRS remained a significant, independent predictor for both the occurrence of acute hypertension on admission and hypertensive episodes within the first 72 h. Conclusions: In acute stroke, decreased BRS was independently associated with the occurrence of acute hypertension on admission. In addition, BRS seemed to be a valid predictor of the BP course in the first 72 h. As some antihypertensives may ameliorate BRS, therapeutic relevance of this finding warrants further attention.